2012
DOI: 10.1161/strokeaha.111.636662
|View full text |Cite
|
Sign up to set email alerts
|

Role of Central Nervous System Periostin in Cerebral Ischemia

Abstract: Background and Purpose-Although periostin, an extracellular matrix glycoprotein, plays pivotal roles in survival, migration, and regeneration in various cells, its expression and function in the brain are still unknown. Here, we investigated the expression and role of periostin in the ischemic brain. Methods-Expression of full-length periostin (periostin 1 [Pn1]) and its splicing variant lacking exon 17 (periostin 2 [Pn2]) was examined by real-time reverse transcription polymerase chain reaction (RT-PCR), West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…At present, clinically important or well-known variants are as follows: POSTN 1, a full-length form containing 23 exons; POSTN 2, which lacks exon 17; POSTN 3, which lacks exon 21; and POSTN 4, which lacks exons 17 and 21 [34]. For example, POSTN 2 exhibited neuroprotective effects and accelerated neurite outgrowth in transient focal cerebral ischemia in mice associated with Akt phosphorylation [35]. On the other hand, in experimental SAH in mice, POSTN 1 caused BBB disruption and brain edema formation [13].…”
Section: Discussionmentioning
confidence: 99%
“…At present, clinically important or well-known variants are as follows: POSTN 1, a full-length form containing 23 exons; POSTN 2, which lacks exon 17; POSTN 3, which lacks exon 21; and POSTN 4, which lacks exons 17 and 21 [34]. For example, POSTN 2 exhibited neuroprotective effects and accelerated neurite outgrowth in transient focal cerebral ischemia in mice associated with Akt phosphorylation [35]. On the other hand, in experimental SAH in mice, POSTN 1 caused BBB disruption and brain edema formation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that periostin 2, not periostin 1 was overexpressed at 24 hours after tMCAo. Exogenously injection of periostin 2 could reduce infarct volume, which indicated that periostin 2 exhibit anti‐hypoxia property and an protective effect . While on the contrary, previous study found that periostin was higher expressed in heart failure and inhibited expression of periostin could increase survival rate, which indicated that inhibition of periostin might be a potential theraphy for heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…15 Periostin was observed in neurons and increased in astrocytes at 24 hours after transient middle cerebral artery occlusion (tMCAo), which indicated that periostin might play an important role in the pathologic process after stroke. 16 Recently, study showed that serum periostin concentrations in patients with traumatic brain injury (TBI) was significantly higher than healthy individuals and level of periostin was significantly associated with clinical severity. 17 While in SAH mouse model, periostin neutralization could alleviate EBI.…”
mentioning
confidence: 99%
“…It has been shown that intracellular Ca 2+ levels were elevated during hypoxic exposure leading to irreversible cell injury while the inhibition of Ca 2+ currents by opioid receptor stimulation by DAMGO, DSLET and ICI-199441, may serve as a neuroprotective mechanism in preventing Ca 2+ overload (Andersen 2004;Bossy-Wetzel et al 2004;Shimamura et al 2012), and this could be the situation with the protection proffered by the µ-, δ-and κ-opioid agonists used in this study. This mechanism of cellular regulation may be utilised during normal cell functioning and in response to oxidative stress like hypoxia (Andersen 2004;Shimamura et al 2012).…”
Section: Discussionmentioning
confidence: 80%
“…This mechanism of cellular regulation may be utilised during normal cell functioning and in response to oxidative stress like hypoxia (Andersen 2004;Shimamura et al 2012). The δ-, µ-and κ-opioid receptors have many similarities such as seven transmembrane domains existing as 60% identical sequences and being coupled to G i/o proteins.…”
Section: Discussionmentioning
confidence: 99%